Emotional Pathways Between Perceived Crowding And Shopping Satisfaction: Evidence From A Creative Pop-Culture Event - Rania Apsari; Berto Mulia Wibawa (Politeknik Internasional Bali, 2026)
This study investigates how perceived crowding influences shopping satisfaction through emotional responses at Comic Frontier (Comifuro), a large-scale creative event in Indonesia. This study, which was established from Stimulus-Organism-Response (S-O-R) framework, differentiates between Human Crowding and Spatial Crowding while exploring how emotional responses Pleasure and Arousal mediate these effects. Data were obtained from 112 shoppers, and the proposed model of the study was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3. Findings indicate that Human Crowding increases both Pleasure and Arousal, whereas Spatial Crowding Decreases Pleasure but does not significantly affect Arousal. Conversely, Spatial Crowding significantly reduces Pleasure but does not affect Arousal. Both human and spatial crowding have indirect positive effects on satisfaction through pleasure. However, arousal showed weaker and inconsistent mediating effects, suggesting that high stimulation does not necessarily increase satisfaction in crowded environments. The analysis revealed full mediation by emotions, emphasizing that emotions serve as the primary pathway linking environmental perception and satisfaction. This study highlights that event success relies on managing physical space to enhance comfort while leveraging the energy of social density. The results provide theoretical support for the S-O-R model in specialized event settings and offer organizers actionable insights for managing high-density environments.